An Integer Programming Approach to the Optimal Product Line Selection Problem - McBride, Richard D.; Zufryden, Fred S. (Marketing Science, 1988)
A zero-one integer mathematical programming formulation is proposed to solve the optimal product line selection problem. Based on individual consumer measurements from conjoint analysis, the formulation seeks to find an optimal subset of products that is drawn from a proposed set of product alternatives with specified product characteristics. In addition to its inherent flexibility in incorporating various realistic constraints, a feature of the proposed approach is its potential determination of verifiable optimal solutions to the product line selection problem. The results of computational experience with an optimization code, known as the X-system, are presented. Using a variety of representative simulated cases, it is shown that the X-system can be used to effectively solve product line selection problems on both mainframe and AT personal computers.